P12 | VISUALIZING NUCLEAR ARCHITECTURE DURING MAMMAL ERYTHROPOIESIS (European Journal of Histochemistry)
The spatial organization of the genome is a highly dynamic phenomenon responsive to multiple endogenous and exogenous stimuli1. Mammalian erythropoiesis is characterized by profound chromatin reorganization prior to nuclear extrusion2, representing a suitable model to investigate nuclear architecture and its impact on gene expression regulation. This study applies transmission electron microscopy combined with cytochemical and immunocytochemical methods for the visualization of key players involved in nuclear remodeling. Morphological analyses revealed major cellular alterations, gradual clearance of cytoplasmic organelles, and spread of heterochromatic regions. The progressive chromatin compaction was assessed through osmium ammine, which enables selective3 DNA visualization and standardized thresholding. Trimethylated H3K9, an epigenetic marker of chromatin condensation, was targeted via immunogold labelling, revealing a stage-dependent increase and relocalization to the perichromatin region. Nuclear complexity was further assessed by RNA visualization, performed with terbium citrate staining, which enables its ultrastructural localization at the single fibril level4, and electron microscopy in situ hybridization selectively labelling pre-mRNAs. Moreover, EDTA regressive staining enabled the visualization of ribonucleoproteins, highlighting their preferential localization in relation to the progressive increase of chromatin condensation. Altogether, this combination of methodologies delineates the coordinated remodelling of the nucleoplasm during erythropoiesis and enables deep investigation of genome features at the nanoscale applicable to further systems.